Two-year outcomes in patients undergoing rotational atherectomy and drug coated balloon therapy for chronic total occluded peripheral arterial diseases: A retrospective cohort study - Ulukan, Mustafa Özer; Karakaya, Atalay; Uğurlucan, Murat; Erkanlı, Korhan (Journal of Surgery and Medicine, 2021)
Background/Aim: Atherectomy is a minimally invasive endovascular surgery technique for removing atherosclerotic plaques in stenosed arteries. It seems to increase the success of angioplasty in the treatment of peripheral artery disease. We aimed to evaluate the outcomes of patients who underwent rotational atherectomy and drug-coated balloon therapy. Methods: In this retrospective cohort study, thirty-four patients who underwent rotational atherectomy and drug-coated balloon angioplasty between August 2016 and January 2019 were evaluated. The Rotablator System (Boston Scientific Corporation; Scimed, Plymouth, MN, USA) was used in all cases. Drug-coated balloons were used in the femoropopliteal section in all patients. Results: The mean age of patients was 65.55 (8.36) years. Seventeen had diabetes mellitus, for which 12 were using oral antidiabetic drugs and 5 were using insulin. At the 3rd postprocedural month, 94.1% of patients (n=32) had no clinical symptoms (P<0.01), two patients needed additional procedures such as balloon angioplasty and stenting due to decreased blood flow and severe stenosis of the superficial femoral artery. At the 1-year follow-up, while 2 patients needed surgery, one needed stenting to the superficial femoral artery. Within 2 years, 27 patients (79.4%) were clinically stable without any symptoms and 2 patients had undergone surgery. Conclusion: Atherectomy devices have become a major tool in the management of peripheral vascular disease. Opening the natural lumen of the arteries gives the patient more time before open vascular surgery.